Brunei in 2015: Oil revenues down, Sharia on the rise - Mueller, Dominik M. (Asian Survey, 2016)
The oil price decline of 2015 caused significant losses for Brunei's economy. The country is still preparing the second phase of its Sharia reform that began in 2014. In addition to his other government positions, Sultan Hassanal Bolkiah appointed himself as minister of foreign affairs and trade, replacing Prince Mohamed Bolkiah.
Created from Fastlane, Scopus look-up
Keywords: Brunei; Fighting corruption; Oil price crisis; Sharia